A Sun within a Sun : The Power and Elegance of Poetry - Lyu, Claire Chi-ah (Book collections on Project MUSE., 2006)
"A Sun within a Sun explores the notions of lightness and weight, discipline and indulgence, freedom and loss of will that are inherent in the poetic enterprise. It poses that lightness, discipline, freedom, and risk are essential for an approach to the enigma of beauty through an elegant shaping of form that holds true not only in poetry but also in pure science and even fashion. Poetry is a language within a language, a heightened and intense awareness of what words mean and what they can do, at its best creating an intensity of a sun within a sun. The poet and reader of poetry must take the risk Icarus took of approaching the sun, for without the risk there is no fulfillment."--Jacket.